NILAI-NILAI PENDIDIKAN KARAKTER DALAM NOVEL PUKAT KARYA TERE LIYE - Sari, Wini Winda; Thahar, Harris Effendi (Universitas Negeri Padang, 2019)
ABSTRACTÂ This study aims to describe the values of character education in the novel Pukat by Tere Liye. This type of research is qualitative research with descriptive methods. The technique of validating the data used in this study is the triangulation technique. This research data is in the form of word, phrases, sentences, and discourses that showcase the action of figures, exposure of the words of the characters and narrators which indicate the values of character education found in the novel Pukat by Tere Liye. The data collection of this research is to read and understand the novel Pukat by Tere Liye as a whole to gain a clear understanding of the contents of the novel, determine the names of characters and the status of figures, inventory data, classify data, and conclude data relating to character education values in the novel Pukat by Tere Liye and guided by appreciative reading. Based on the results of the research, it can be concluded that the values of character education in the novel Pukat by Tere Liye, namely the values of religious character education, the value of honest character education, the value of character tolerance education, the value of education of hard-working characters, the value of creative character education, the value of independent character education, the value of curious character education, the value of friendly/communicative character education, the value of peace-loving character education, the value of reading character-loving education, the value social care character education, the value of character education responsibility, and the value of discipline character education. The value of character education is dominant in the novel Pukat by Tere Liye, which is 13 values of religioun character education. Then, the results of this study can be implicated in Indonesian language learning and other learning both in the classroom and outside the classroom.Â Kata kunci: Nilai, Pendidikan Karakter, Novel Pukat